Nonequilibrium Liquid Crystalline Layered Phase Stabilized by Light - Hegde, Gurumurthy; Prasad, S. Krishna; Nair, Geetha G. (American Chemical Society, 2007)
The ability of light to alter/stabilize a particular thermodynamic phase is a power tool to investigate condensed matter from a new dimension. This field of photoinduced phase transitions is currently an important area of research. Being elastically soft and having subtle changes between its many phases a liquid crystal material is an attractive medium to investigate such light-driven phase transitions. The attraction is partly due to the large birefringence changes accompanying these transitions that are useful in developing photonic devices.In all of the cases reported to date, the photoinduced transition always leads to a phase that in any case exists in the thermal cycle. Recently we reported the first exception to such an established phenomenon (AdV. Mater. 2005, 17, 2086). The guest-host ternary mixture consisting of the photoactive azobenzene guest molecules does not exhibit smectic A phase in the absence of UV radiation. However, the smectic A phase is induced and stabilized only in the presence of UV light. In this paper, we map out hitherto unexplored temperature versus UV intensity phase diagrams for various mixtures, which illustrate that light mimics, in a limited sense, the role of a thermodynamic parameter such as, for example, pressure. The threshold UV intensity required to photodrive the appearance of the smectic A phase is seen to have a strong concentration dependence. Our studies also suggest the possibility of observing a double critical point by employing the UV intensity as a fine-tuning parameter.